Driverless finance : fintech's impact on financial stability - Allen, Hilary J. (New York, NY : Oxford University Press, 2022)
'Driverless Finance' explores the threats that different fintech innovations pose for our financial system. With in-depth and accessible descriptions of new financial technologies and business models - ranging from distributed ledgers to machine learning, cryptoassets to robo-investing - this book allows readers to think more critically about fintech, and about how the law should respond to it.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on March 8, 2022).
Keywords: Financial services industry -- Law and legislation; Financial services industry -- Technological innovations